Reversible fluorescence sensing: BODIPY integrated silica nanoparticles for the sensitive and selective “turn-off” detection of Au (III) ions in fully aqueous media - Demirbilek, Nisa; Karakus, Aysenur Cataler; Erdemir, Eda; Hamur, Beyza; Nasibov, Humbat; Karakuş, Erman (Elsevier B.V., 2025)
Gold ion species, including various oxidation states such as Au(I) and Au(III), exhibit extraordinary properties in both chemical and biological processes. Nevertheless, excessive amounts of gold ions, particularly Au3+, can pose significant risks to living organisms. Especially, high concentrations (around 200 ?M) of Au3+ ions can be highly toxic. Given the potential hazards, there is an urgent need for precise and sensitive methods to detect these ions in various environments. In this work, a highly efficient and novel BODIPY functionalised fluorescent silica nanoparticle-based probe has been developed for the selective and sensitive detection of Au3+ ions. A BODIPY scaffold was chosen as a signal reporter unit and covalently attached to silica nanoparticles. The probe, BOD–SiNP, demonstrated a reversible “turn-off” fluorometric response with high sensitivity (LOD = 48 nM). Density Functional Theory (DFT) calculations were used to analyse the structure of the sensing system. Also, BOD–SiNP successfully detected Au3+ ions in real water samples. It is the first study to explore the use of silica nanoparticle-based systems for the fluorometric reversible detection of Au3+ ions. © 2025 Elsevier B.V., All rights reserved.
Keywords: BODIPY; Fluorescent dye; Gold ion detection; Nanoprobe; Silica nanoparticles